2017
DOI: 10.1007/s00405-017-4575-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplasia and the degree and activity of inflammation in chronic recurrent tonsillitis: a histopathological study

Abstract: Postoperative haemorrhage following tonsillectomy occurs in 5.98% of all cases with up to 10 deaths reported annually in Germany. When comparing tonsillectomy (TE) and tonsillotomy (TT), the same long-term frequency of ENT infections is displayed in children and young adults. However, taking postoperative haemorrhaging into account, TT is more favourable. Chronic tonsillitis is one of the most common indications for TE in the adult population; however, a histopathological characterization may reveal objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
5
0
6
Order By: Relevance
“…They concluded that the grade of inflammation and activity, as well as the follicular hyperplasia in higher graded inflammatory processes is located more in the basal parts of the tonsils. 5…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the grade of inflammation and activity, as well as the follicular hyperplasia in higher graded inflammatory processes is located more in the basal parts of the tonsils. 5…”
Section: Discussionmentioning
confidence: 99%
“…N/A : Data tidak tersedia Beberapa studi yang teridentifikasi menyatakan usia dan status kebersihan mulut dapat menjadi suatu indikator yang dapat mempengaruhi pembesaran ukuran tonsil palatina. [9], [11], [16]- [19] , [20], [21], [23]- [26] , [29] Oral hygiene yang buruk merupakan salah satu faktor resiko pembesaran ukuran tonsil palatina ditambah dengan penurunan sistem imunitas tubuh seiring bertambahnya usia. Hal ini sesuai dengan penelitian Adetayo pada subjek usia 16-48 tahun ditemukan status kebersihan mulut yang buruk sebanyak 61 orang (76,30%).…”
Section: Halitosis As An Indicationunclassified
“…Beberapa penelitian menunjukkan bahwa biofilm dapat terjadi hampir pada semua jaringan tubuh manusia termasuk tonsil. [20] Biofilm merupakan suatu lapisan struktur mikroorganisme yang bersifat kompleks, terintegrasi, dan menempel pada permukaan makhluk hidup yang diselimuti oleh matriks ekstraseluler dan berfungsi sebagai mekanisme pertahanan dari faktor eksternal yang dibentuk oleh mikroorganisme itu sendiri. Matriks ekstraseluler inilah yang menjadi faktor utama pembeda biofilm dengan kolonisasi bakteri lainnya.…”
Section: Halitosis As An Indicationunclassified
See 1 more Smart Citation
“…Consequently, regulating fibrogenic processes may be significant therapeutic option in diseases associated with chronic inflammation 27 .…”
mentioning
confidence: 99%